2017
DOI: 10.3233/trd-170016
|View full text |Cite
|
Sign up to set email alerts
|

Creating a multi-center rare disease consortium – the Consortium of Eosinophilic Gastrointestinal Disease Researchers (CEGIR)

Abstract: Eosinophilic gastrointestinal disorders (EGIDs) affect various segments of the gastrointestinal tract. Since these disorders are rare, collaboration is essential to enroll subjects in clinical studies and study the broader population. The Rare Diseases Clinical Research Network (RDCRN), a program of the National Center for Advancing Translational Sciences (NCATS), funded the Consortium of Eosinophilic Gastrointestinal Disease Researchers (CEGIR) in 2014 to advance the field of EGIDs. CEGIR facilitates collabor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6
1

Relationship

6
1

Authors

Journals

citations
Cited by 29 publications
(42 citation statements)
references
References 43 publications
0
42
0
Order By: Relevance
“…RDCRN has collaborated with PAGs and the pharmaceutical industry on government‐sponsored clinical research studies to be completed in a timely fashion and to bring novel therapeutics to market. An EAD‐associated registry was borne out of RDCRN through the CEGIR (U54 AI117804), an initiative of the Office of Rare Disease Research (ORDR) that is jointly funded by NCATS, NIAID, and NIDDK . This registry (part of a longitudinal observational study) is designed to understand the natural history of EGID and will help standardize histopathologic evaluation and assessment of these rare disorders.…”
Section: Resultsmentioning
confidence: 99%
“…RDCRN has collaborated with PAGs and the pharmaceutical industry on government‐sponsored clinical research studies to be completed in a timely fashion and to bring novel therapeutics to market. An EAD‐associated registry was borne out of RDCRN through the CEGIR (U54 AI117804), an initiative of the Office of Rare Disease Research (ORDR) that is jointly funded by NCATS, NIAID, and NIDDK . This registry (part of a longitudinal observational study) is designed to understand the natural history of EGID and will help standardize histopathologic evaluation and assessment of these rare disorders.…”
Section: Resultsmentioning
confidence: 99%
“…This study presents one of the first formal applications of previous data to inform the theory based creation of a comprehensive approach to conducting Web-based direct-to-patient recruitment for research. The development of PRISM builds upon the positive findings in the TAPIR trial, seeks to avoid the challenges identified in the approach used for TAPIR, and advances innovative approaches to clinical research by: (1) expanding the use of social media and other online recruitment strategies through the use of novel technologies and marketing campaigns to target populations of patients with rare diseases previously unavailable to researchers [20][21][22][23][24]; (2) identifying and attempting to remove barriers to enrollment and participation in clinical research studies through web-based referral [53]; and (3) demonstrating the feasibility of the proposed methods for clinical research studies in rare disease populations.…”
Section: Discussionmentioning
confidence: 99%
“…A principal component of our strategy relied upon soliciting buy-in and commitment from PAG representatives to share and promote our recruitment content via their respective social media platform accounts in order to further promote our efforts. As previously reported by the RDCRN, PAGs act as research partners in ensuring the feasibility and success of various protocols via their collaboration with patient recruitment, support training programs, and study design [2,44]. PAG representatives were asked to provide what they felt would be the most important information to be considered about their respective target population, including the population's geographic characteristics, imagery or messaging that should be utilized or avoided, and most successful recruitment strategies to date.…”
Section: Pag Involvementmentioning
confidence: 99%
See 1 more Smart Citation
“…We conducted a retrospective study of subjects from multiple centers in the Consortium of Eosinophilic Gastrointestinal Disease Researchers (CEGIR) 19-20 , including pediatric and adult tertiary care centers in different geographical regions. Subjects were included from the University of Arkansas for Medical Sciences/Arkansas Children’s Hospital, the University of North Carolina, Children’s Hospital of Philadelphia, Cincinnati Children’s Hospital Medical Center, the University of Pennsylvania, and Children’s Hospital of Colorado.…”
Section: Methodsmentioning
confidence: 99%